Atividades lúdicas entre adultos jovens: um estudo com universitários capixabas - Pylro, Simone Chabudee (2004)
The intention of this research was to investigate the favorite ludic activities carried out by young adults. The investigation employed a questionnaire, applied to 213 Capixaba university students aged between 20 and 40 years old, to find out if the differentiation in ludic preference evidences in adulthood, in function of the gender. It was verified that, on a daily basis, very little time was dedicated to games and play. The favorite activities were dating, being with friends, going to the movies, listening to music and watching TV. Amongst the men, typical activities were soccer and aggressive games/ playing activities. Ludic activities considered typically female were mainly related to symbolic games. Among the reasons causing difficulties for ludic activities, the most prominent were work, study and fatigue. It was evident the notorious differences, according to gender, regarding the ludic activities performed, as well as the time dedicated to such, in function of gender.